Технологія ректифікації в режимі керованих циклів - Булій, Юрій Володимирович; Шиян, Петро Леонідович; Дмитрук, Аркадій Павлович; Малигін, А. І. (My University, 2013)
Запропонована технологія ректифікації в режимі керованих циклів затримки рідини на тарілках та синхронного її переливу з тарілки на тарілку по всій висоті колонного апарата за заданим алгоритмом при безперервній подачі в апарат пари та рідини. Впровадження інноваційної технології у виробництво дозволяє підвищити ефективність міжфазового контакту і знизити витрати гріючої пари на процес ректифікації на 40 %. Work of the known columnar vehicles is analysed with the controlled cycles of rectification. The brought results over of productive tests of technology of the guided rectification that envisages flowing of liquid from a dish on a dish through a transitional capacity at the change of pressure of steam stream. Indicated advantages and lacks of technology. More perfect technology of rectification is offered in the mode of the guided delay of liquid on piattis and her synchronous flowing loops from a dish on a dish on all height of column due to the additionally set movable valves, related to the drive mechanisms the action of that takes place after the set algorithm in accordance with the program of inspector. Time of stay of phases is on a dish, necessary for the complete satiation of pair the easily volatile components of liquid, and liquids - by the difficult volatile components of pair, it is determined experimentally. Introduction of innovative technology in an alcoholic production allows to promote efficiency of line-to-line contact and decrease expenses warming pair on the process of rectification on 40 %. One of possible variants is schematically shown her realizayion.
Keywords: переливні пристрої; ректифікаційна колона; керовані цикли; ректифікація; фазова рівновага; масообмін; flowing devices; column of rectification; guided cycles; rectification; phase equilibrium; mass transfer; кафедра біотехнології продуктів бродіння і виноробства